Incidence rate and risk factors of status epilepticus after stroke. (October 2021) - Wang, Haijiao; Chen, Deng; Tan, Ge; Zhu, Li Na; Liu, Ling
Highlights: The crude overall rate of SE after stroke was 6.90 per 1000 strokes. African American race, alcohol abuse and renal disease are associated with an increased risk of PSSE. The proportion of patients with hypertension and diabetes was higher in patients without PSSE than in patients with PSSE. Abstract: Purpose To evaluate the incidence rate and risk factors for status epilepticus (SE) after stroke (PSSE), including ischaemic stroke (IS), intracerebral hemorrhage (ICH), and subarachnoid hemorrhage (SAH). Methods A meta-analysis was performed using relevant research from databases such as PubMed, Embase, Cochrane Online Library, and Clinicaltrials.gov. The quality of the studies was evaluated by using the quality evaluation criteria of the Agency for Healthcare Research and Quality (AHRQ). All data were pooled by STATA 12.0 software for meta-analysis. Results The review considered 1650 articles, and 17 articles with 2821 instances of SE among 1088087 instances of stroke were included. The incidence rate of SE after stroke was 6.90 per 1000 total strokes (95% CI: 5.58–8.22). By subgroup analysis of SE, the rates were 33.85‰ (95% CI: 13.77–53.94) for non-convulsive status epilepticus (NCSE) and 2.42‰ (95%CI: 1.66–3.19) for generalized convulsive status epilepticus (GCSE). Age, sex, and presence of atrial fibrillation showed no significant difference between the SE group and the non-SE group after stroke. Hypertension and diabetes are associated with a decreased rate of SE. However, African American race, alcohol abuse, and renal disease are associated with an increased rate of SE. Significance There were approximately 6.9 patients with status epilepticus per 1000 strokes. NCSE is more common after stroke and needs more attention. African American race, alcohol abuse and renal disease may be risk factors for PSSE.